Digital journalism in 2008 - Guallar, Javier (Anuario ThinkEPI, 2009)
Review of the state of digital newspapers in Spain in 2008, considering the following aspects: media crisis, the end of an era, media and social networks, microblogging, widgets, and free access to digital archives.
Keywords: Digital media; Digital newspapers; Online newspapers; Social networks; Microblogging; Widgets; Digital press archives; Spain.